FREQUENCY OF CHRONIC COMMON SOMATIC PATHOLOGY IN THE WORKERS OF MAIN PROFESSIONS OF COAL MINING ENTERPRISES OF THE SOUTH OF KUZBASS - Ольга Юрьевна Коротенко; Егор Сергеевич Филимонов; Ольга Николаевна Блажина; Евгения Викторовна Уланова (Медицина в Кузбассе)
Subject of the study. 1563 workers of the mines in the South of Kuzbass were examined: men aged from 22 to 60 years who were divided into 2 professional groups depending on the classes of danger and harmfulness, on subgroups by age (from 22 to 30 years, from 31 to 40 years, more than 40 years) and work experience (up to 10 years, from 11 to 20 years, over 20 years).